Reduction of Environmental Contamination With Multidrug-Resistant Bacteria by Copper-Alloy Coating of Surfaces in a Highly Endemic Setting. (5th May 2017) - Souli, Maria; Antoniadou, Anastasia; Katsarolis, Ioannis; Mavrou, Irini; Paramythiotou, Elisabeth; Papadomichelakis, Evangelos; Drogari-Apiranthitou, Maria; Panagea, Theofano; Giamarellou, Helen; Petrikkos, George; Armaganidis, Apostolos
Abstract : OBJECTIVE: To evaluate the efficacy of copper-coating in reducing environmental colonization in an intensive-care unit (ICU) with multidrug-resistant-organism (MDRO) endemicity DESIGN: Interventional, comparative crossover trial SETTING: The general ICU of Attikon University hospital in Athens, Greece PATIENTS: Those admitted to ICU compartments A and B during the study period METHODS: Before any intervention (phase 1), the optimum sampling method using 2 nylon swabs was validated. In phase 2, 6 copper-coated beds (ie, with coated upper, lower, and side rails) and accessories (ie, coated side table, intravenous [i.v.] pole stands, side-cart handles, and manual antiseptic dispenser cover) were introduced as follows: During phase 2a (September 2011 to February 2012), coated items were placed next to noncoated ones (controls) in both compartments A and B; during phase 2b (May 2012 to January 2013), all copper-coated items were placed in compartment A, and all noncoated ones (controls) in compartment B. Patients were randomly assigned to available beds. Environmental samples were cultured quantitatively for clinically important bacteria. Clinical and demographic data were collected from medical records. RESULTS: Copper coating significantly reduced the percentage of colonized surfaces (55.6% vs 72.5%; P <.0001), the percentage of surfaces colonized by MDR gram-negative bacteria (13.8% vs 22.7%; P =.003) or by enterococci (4% vs 17%; P =.014), the total bioburden (2, 858 vs 7, 631 cfu/100 cm 2 ; P =.008), and the bioburden of gram-negative isolates, specifically (261 vs 1, 266 cfu/100 cm 2 ; P =.049). This effect was more pronounced when the ratio of coated surfaces around the patient was increased (phase 2b). CONCLUSIONS: Copper-coated items in an ICU setting with endemic high antimicrobial resistance reduced environmental colonization by MDROs. Infect Control Hosp Epidemiol 2017;38:765–771